Prognostic utility of MELD‐XI in adult congenital heart disease patients undergoing cardiac transplantation. Issue 6 (7th May 2018) - Adams, Evan D.; Jackson, Nicholas J.; Young, Tim; DePasquale, Eugene C.; Reardon, Leigh C.
Abstract: Background: Model of End‐Stage Liver Disease eXcluding INR (MELD‐XI) at cardiac transplant has demonstrated prognostic survival utility, but has not been specifically validated in adult congenital heart disease (ACHD) in a registry study. Methods: Adults undergoing first‐time orthotopic heart transplant from 2005 to 2015 in the United Network for Organ Sharing (UNOS) registry were examined in parallel: ACHD (n = 543), ischemic‐dilated cardiomyopathy (IDCM, n = 6954) and valvular heart disease (VHD, n = 355). Our primary endpoint was a composite of death, graft failure, and retransplantation assessed at 3 months (early), and those with freedom from early endpoint were reassessed at 5 years (late). Interactions between hepatorenal indices and waitlist time were examined. Secondary outcomes relating to long‐term morbidity were assessed at late endpoint. Freedom from endpoint analysis in ACHD at clinically relevant endpoints was also conducted. Results: Model of End‐Stage Liver Disease eXcluding INR score at transplant associated with an increased risk of early endpoint in all cohorts. At late endpoint, bilirubin level associated with increased risk uniquely in ACHD. Conclusions: Model of End‐Stage Liver Disease eXcluding INR holds prognostic application to ACHD in early time points and demonstrates unique waitlist interactions. Transplant bilirubin level may hold significance in long‐term risk stratification of the ACHD population. Time on waitlist is an important consideration to contextualize these values.